Geothermal energy in deep aquifers: A global assessment of the resource base for direct heat utilization. (February 2018) - Limberger, Jon; Boxem, Thijs; Pluymaekers, Maarten; Bruhn, David; Manzella, Adele; Calcagno, Philippe; Beekman, Fred; Cloetingh, Sierd; van Wees, Jan-Diederik
Abstract: In this paper we present results of a global resource assessment for geothermal energy within deep aquifers for direct heat utilization. Greenhouse heating, spatial heating, and spatial cooling are considered in this assessment. We derive subsurface temperatures from geophysical data and apply a volumetric heat-in-place method to improve current global geothermal resource base estimates for direct heat applications. The amount of thermal energy stored within aquifers depends on the Earth's heat flow, aquifer volume, and thermal properties. We assess the thermal energy available by estimating subsurface temperatures up to a depth of three kilometer depending on aquifer thickness. The distribution of geothermal resources is displayed in a series of maps and the depth of the minimum production temperature is used as an indicator of performance and technical feasibility. Suitable aquifers underlay 16% of the Earth's land surface and store an estimated 4·10 5 to 5·10 6 EJ that could theoretically be used for direct heat applications. Even with a conservative recovery factor of 1% and an assumed lifetime of 30 years, the annual recoverable geothermal energy is in the same order as the world final energy consumption of 363.5 EJ yr −1 . Although the amount of geothermal energy stored in aquifers is vast, geothermal direct heat applications are currently underdeveloped with less than one thousandth of their technical potential used.